Interaction of Isonicotinic Acid Hydrazide with Carboxylic Acid Anhydrides - Nurkenov, O.A.; Fazylov, S.D.; Seilkhanov, T.M.; Abulyaissova, L.K.; Turdybekov, K.M.; Zhivotova, T.S.; Kabieva, S.K.; Mendibayeva, A.Zh. (Eurasian Journal of Chemistry, 2023)
There has been presented data on the synthesis of monoamides and cyclic imides which are derivatives of isonicotinic acid hydrazide. Cyclic anhydrides of carboxylic acids (succinic, maleic and phthalic) easily react with the hydrazide of isonicotinic acid with cycle opening, forming isonicotinoylhydrazide of dicarboxylic acids, and under more severe conditions the latter are transformed into cyclic acid imides. The structures of the synthesized compounds were studied using 1H- and 13C-NMR spectroscopy, as well as data from two-dimensional COSY (1H-1H) and HMQC (1H-13C) spectra. The values of chemical shifts, multiplicity and in-tegral intensity of 1H and 13C signals in one-dimensional NMR spectra were determined. Homo- and heteronuclear interactions confirming the structure of the studied compounds were established using spectra in the COSY (1H-1H) and HMQC (1H-13C) formats. In the approximation of the density functional B3LYP with a base set of 6-31G(d), the enthalpy of the reactions ΔHr in the absence and in the presence of a sol-vent — isopropanol (self-consistent reaction field method) were calculated quantum-chemically.
Keywords: isonicotinic acid hydrazide; anhydrides; 1,4-dicarboxylic acid monoamide; phthalic acid acylhydrazides; cyclic imides; quantum chemical calculation; heteronuclear interactions; NMR spectroscopy